Knowledge and Power in Indonesian Traditional Music: A Genealogical Approach on the Transformation of the Meaning of Karawitan - Ji Pyo Chung (Universitas Gadjah Mada, 2023)
The term Karawitan is generally known to mean gamelan music, more specifically Javanese, Balinese, and Sundanese gamelan music tuned to slendro and pelog scales. However, the term is discursive and has meaning in wider contexts as well. The term karawitan first appeared during the colonial period in royal courts on Java to indicate Javanese gamelan music. However, through its nation-wide university karawitan programs, the Indonesian government and art academics use the term to refer to all Indonesian traditional music practices (Musik Nusantara).Thisarticle gives a postcolonial account of the discourse surrounding the term karawitan to trace the transformation of its meaning. It employs Michel Foucault's theory of discourse and genealogical research methods to explore colonial-era and post-colonial literature using the term karawitan. By reviewing various discourses about karawitan, authors provide a more nuanced understanding about how power operates in the context of traditional music in Indonesia. We illustrate how the meaning of “karawitan” has been re-defined and contested through discursive practices. In general, these transformations demonstrate a shift from colonial power to national power